Procedural Music in Games - Ayres, José Eduardo; Arthur, Pedro; Rolla, Vitor; Velho, Luiz (Anais do Simpósio Brasileiro de Computação Musical (SBCM), 2019)
This workshop will bring to the audience an introduction to the Chuck audio programming language, to the Unity game engine within a hands-on experience how one can use such technologies to achieve a new level of immersion through procedural generated sounds responding to game events and visual effects. The workshop is intended to a broad audience ranging from programmers to ones with little to no knowledge in the field.